2014
DOI: 10.5539/ass.v11n2p154
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Life Satisfaction among Caregivers of Children with Developmental Disabilities in South Korea

Abstract: It is known that factors such as socio-demographic characteristics and care-related stressors among caregivers of children with developmental disabilities (CDD) predict their life satisfaction (LS). Due to a lack of data, however, very little is known about the predictors of LS in South Korea. This study aims to examine factors associated with LS among the caregivers of CDD using the recently collected data from the national survey on people with developmental disabilities in South Korea. Structural Equation M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
6
0
7
Order By: Relevance
“…This finding is in accordance with a study in South Korea which similarly found older caregivers reported lower life satisfaction. The growing needs of children with disabilities and the worsening physical health of the caregivers as their age increases, coupled with fatigue due to long periods of care, ultimately caused a decline in life satisfaction amongst the caregivers ( 36 ). Interestingly, our study found that the financial support received by family caregivers had an indirect negative effect on QoL through perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in accordance with a study in South Korea which similarly found older caregivers reported lower life satisfaction. The growing needs of children with disabilities and the worsening physical health of the caregivers as their age increases, coupled with fatigue due to long periods of care, ultimately caused a decline in life satisfaction amongst the caregivers ( 36 ). Interestingly, our study found that the financial support received by family caregivers had an indirect negative effect on QoL through perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is a 29-item scale with 5-point Likert rating ranging from 0 to 4. It consists of five subscales including, Burden in the relationship (1,8,11,14,18,20), Emotional well-being (2,4,5,9,10,21,22), Social and family life (3, 6, 12, 13), Finances (15), and Loss of control over one's life (7,16,17,19). It has a good internal reliability (Cronbach alpha 13 coefficient of 0.92).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, there are various studies investigating the life satisfaction of parents of children with disabilities. For example, life satisfaction levels of parents of children with Down Syndrome were examined by Sloper et al (1991), with ID and PD by Akandere et al (2009), with cerebral palsy and ASD by Gülaldı (2010), with ID by Sarıkaya (2011), with disabilities by Darling et al (2012), with ASD, ID, physical disabilities and Down syndrome by Kantar (2014), with and without developmental disabilities by Huang et al (2014), with ASD and ID by Cho and Kahng (2015), with ID and typical development by Yavuz (2016), with ASD, ID and other developmental disabilities by Çattık and Aksoy (2018), and parents of children with ID were examined by Avşaroğlu and Okutan (2018), a limited number of studies examined the relationship between family resilience of children with disabilities and their life satisfaction Palancı (2018) and Openshaw (2011) examined the relationship between life satisfaction of individuals with disabilities and family resilience. Demiray (2019) examined the relationship between the life quality of parents of children with special needs and family resilience.…”
Section: Introductionmentioning
confidence: 99%